Theory:

Let us learn how to find the slope using the given equation.
 
To find the slope of the equation, let us write the equation in the format of \(y=mx+c\) where \(m\) is the slope of the equation and \(c\) is the \(y\) - intercept.
Example:
Find the slope of the equation \(4x-6y=12\)
 
Solution:
 
The given equation is \(4x-6y=12\).
 
Now, let us write the equation in the form of \(y=mx+c\).
 
\(4x-6y-4x=12-4x\) (Subtract both sides by \(4x\))
 
\(-6y=12-4x\)
 
\(y=\frac{12}{-6}-\frac{4x}{-6}\) (Divide both sides of the equation by \(-6\))
 
\(y=-2+\frac{2x}{3}\)
 
Rearranging the above equation, we have:
 
\(y=\frac{2x}{3}-2\)
 
Now, comparing the above equation with \(y=mx+c\), we have:
 
\(m=\frac{2}{3}\)
 
Therefore, the slope of the given equation is \(\frac{2}{3}\).